Precursors of satisfaction with Bachelor Dissertation among psychology undergraduated students from University of Sevilla (Spain) - M. Valdés Díaz; J. López-Cepero Borrego (Universitat Politècnica de València, 2019)
Since Spanish study plans were adapted to European Higher Education Area (EHEA), Bachelor Dissertations became mandatory in order to obtain a Degree in Psychology. Thereby, the Faculty of Psychology at University of Seville (Spain) devotes six credits (150 hours) to develop this dissertation along the fourth course. Present work focusses in personal experiences related to making up the Bachelor Dissertation, assessing the role that different variables play on satisfaction among Sevillian psychology undergraduate students. Participants were 207 students who completed the course in the 2014-15 academic year, out of a total of 270 students enrolled (76.7%). A pencil-and-paper questionnaire was administered, gathering information about the assignment of tutors, need for support, difficulties found and satisfaction with the process. Around  one third of the students completed their Bachelor Dissertation with advisors (tutors) of their choice. 50% of the participants made at least 5 consultations (telematic or in person) to their tutors throughout the course, and 9% indicated that they made at least 8 queries in both ways. More than 50% of participants reported having difficulties designing the work and/or analyzing results. However, 83% of students considered the dissertation an interesting challenge. A linear regression showed that the amount of time dedicated, its perceived utility and the possibility of transferring the results to the labor field were precursors of the positive evaluation of the process. The desirability of designing specific training actions and reinforcing the transfer of knowledge as a way to improve  the student experience in Bachelor dissertation is discussed.